2017
DOI: 10.1176/appi.ajp.2016.15111403
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Social Networks After Disaster

Abstract: These findings provide the first evidence of disorder-specific patterns in relation to one's social connections after disaster. Depression appears to co-occur in linked individuals, whereas PTSD risk is increased with social fragmentation. These patterns underscore the need to adopt a sociocentric perspective of postdisaster mental health in order to better understand the potential for societal interventions in the wake of disaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 57 publications
7
84
0
Order By: Relevance
“…Those who received support only from formal sources, not from personal connections, reported lowest post‐disaster satisfaction with life.3. Bryant et al () Assessed the extent to which mental health outcomes after the disaster were associated with social network structures. (Same sample as 12)Event: Black Saturday bushfires, February 2009 Country: Australia Age: adults (mean=57.1) Sample size: 558 Sampling: non‐random Diversity: 57 per cent female; other factors unspecifiedDesign: cross‐sectional Time: between two and four years after Support measures: social embeddedness aspects of social networks were assessed by asking respondents to nominate people with whom they felt personally close. A social network map was constructed that showed participants’ ties to other participants (method‐based)More close ties was associated with less depression and less risk of PTSD ( direct effect ).…”
Section: Annexesmentioning
confidence: 99%
“…Those who received support only from formal sources, not from personal connections, reported lowest post‐disaster satisfaction with life.3. Bryant et al () Assessed the extent to which mental health outcomes after the disaster were associated with social network structures. (Same sample as 12)Event: Black Saturday bushfires, February 2009 Country: Australia Age: adults (mean=57.1) Sample size: 558 Sampling: non‐random Diversity: 57 per cent female; other factors unspecifiedDesign: cross‐sectional Time: between two and four years after Support measures: social embeddedness aspects of social networks were assessed by asking respondents to nominate people with whom they felt personally close. A social network map was constructed that showed participants’ ties to other participants (method‐based)More close ties was associated with less depression and less risk of PTSD ( direct effect ).…”
Section: Annexesmentioning
confidence: 99%
“…As is evident from the description above, the investigators' primary interest in the broader Beyond Bushfires study was exploring the influence that social networks and social environments had on the recovery trajectories of individuals and communities and we designed our survey instruments to capture these phenomena. As hypothesized, we found that people's networks, level of social connectedness, and group involvement did have an impact on their mental health (Bryant et al, 2017;Gallagher et al, 2019). The qualitative component of the study however, consistent with commonly accepted inductive qualitative research paradigms, was explicitly designed (using open-ended research probes) to be driven more by the interests of the participants than those of the researchers.…”
Section: Introductionmentioning
confidence: 64%
“…This scale was with a total of 10 items and marked with 5 points, among which items 4, 5, 7 and 8 were reversely scored. The results of PSS-10 are as follows: mild (0-14), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), moderately severe (26)(27)(28)(29)(30)(31) and severe (32-40) stress. In order to lter severe cases, the cutoff scores for GAD-7, PHQ-9 and PSS-10 were 5, 5 and 15 respectively, which predicts detecting symptoms of anxiety, depression and stress if scores were higher than this criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Though COVID-19 has been eased effectively in China, there are still individuals stricken with serious mental disorders [33]. Individuals suffering from severe mental trauma have a high hazard to develop PTSD [34], but an earlier study showed that psychological interventions are bene cial to reduce anxiety and depression during disasters, and is good for them to develop personal strategies for coping with crisis [28].…”
Section: Intervention Strategies Of Mental Health For Social Agenciesmentioning
confidence: 99%
See 1 more Smart Citation